Unusual weather over northwest & west India during November, 2010 - YADAV, BP; KUMAR, NARESH; KHOLE, MEDHA (MAUSAM, 2013)
lkekU;r% uoEcj dk eghuk /kwi ds fnuksa o fcuk ckfj’k okyk eghuk dgykrk gS vkSj uoEcj eghus ds chrus ds lkFk-lkFk mRrj if’peh Hkkjr ds eSnkuh Hkkxksa esa lqcg dh gYdh BaMd fy, ekSle lqgkouk jgrk gS fdUrq uoEcj 2010 ds nkSjku mRrj if’peh vkSj if’pe Hkkjr esa o"kkZ dh ckSNkjksa ds lkFk yEcs le; rd yxkrkj ckny Nk, jgs ftlds dkj.k ekSle vlkekU; jgkA bl vlkekU; ekSle ds fy, mRrjnk;h HkkSfrd izfØ;kvksa dk irk yxkus ds fy, bl ’kks/k i= esa bl ekg esa cuh flukfIVd fLFkfr;ksa dk foLr`r fo’ys"k.k fd;k x;k gSA bl v/;;u ls ;g irk pyk gS fd vjc lkxj esa xgu fuEu vonkc iz.kkyh dh mifLFkfr vkSj fupys Lrjksa esa if’peh gokvksa esa e/; kksHkeaMyh; nzksf.k;ksa ds lkFk&lkFk iwohZ gokvksa esa mPp vk;keh nzksf.k;ksa dh ijLij fØ;kvksa ds dkj.k uoEcj ekg esa ekSle vlkekU; jgkA Generally, November is the dry month with sunny days and pleasant weather for plains of northwest & west India with a bit of early morning chill as the month progresses. But during November, 2010, there was unusual weather in the form of prolonged and persistent cloudy conditions with wet spell over northwest & west India. To find out the physical processes leading to this unusual weather, detailed analysis of synoptic conditions during the month has been carried out in this paper. This study reveals that the unusual weather that occurred in association with presence of an intense low pressure system in the Arabian Sea and interaction of high-amplitude troughs in easterlies in the lower levels with mid-tropospheric troughs in the westerlies.